Pengaruh Karakteristik Sosial Demografi Dan Brand Image Terhadap Keputusan Pembelian Smartphone Merek Blackberry - pramadi, ditya; Suryani, Alit (E-Jurnal Manajemen, 2013)
Blackberry is one of the means of communication or often called smartphones growing in Indonesia. Since the beginning penetration in 2004, a lot of the Blackberry smartphone reap success and can be a top leader in the sale of its products in Indonesia. The purpose of this study is to investigate and analyze the influence of demographic and social characteristics of the brand image (brand image) on purchase decisions Blackberry smartphone brand in the area of Denpasar. The research was conducted in the city of Denpasar. The variables studied were demographics, brand image, and purchasing decisions. The sampling technique used was based on purposive sampling with total respondent 110 users of smartphone Blackberry. The data analysis technique used is Structural Equation Modelling or SEM. Based on the survey results revealed that: 1) demographic variable has a positive and significant impact on purchasing decisions. 2) Variable brand image has a positive and significant impact on purchasing decisions. The results of this study are expected to provide a feedback for RIM (Research In Motion) which is a produsen of smartphone Blackberry that demographic and brand image influence a purchase decision of Blackberry.